Determinan Pertumbuhan laba Kelompok Saham Aktif - Gunawan, Philip Austin; Hardiningsih, Pancawati (Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims to analyze influence of liquidity, leverage, profitability and activity on profit growth in active company group in 2018-2022. The selected sample was 175 observations using the purpose sampling method. This research uses multiple linear regression analysis. The test results show that in the LQ45 group liquidity and profitability has positive effect on profit growth. Meanwhile for JII group, liquidity, profitability and the activity has a positive effect on profit growth. Company size shows it strengthens the influence of liquidity on profit growth in LQ45 and JII share groups.